The interaction discrepancy model: a theoretical framework for understanding person-environment interactions - Umbra, Robin; Fasbender, Ulrike (Frontiers in Psychology, 2025)
This manuscript introduces the Interaction Discrepancy Model (IDM), a theoretical framework designed to enhance our understanding of person-environment interactions. Traditional models often overlook the dynamic, iterative, and feedback-driven nature of these interactions, typically focusing on episodic and isolated psychological processes and conscious mechanisms. The IDM addresses these limitations by integrating the dynamics of cognitive, affective, and behavioral processes at both conscious and non-conscious levels. The model outlines an eight-stage process: (1) perception, (2) interaction construal, (3) verification, (4) congruence/discrepancy, (5) appraisal, (6) autoregulatory response, (7) action plan, and (8) feedback. This comprehensive approach seeks to explain the varied responses observed in empirical research and real-life scenarios. The IDM’s applicability extends across multiple contexts, including aggression, delinquency, conflict management, and industrial-organizational psychology, emphasizing the critical role of perceived discrepancies in triggering affective and behavioral responses. By incorporating contextual factors and providing a structured framework for falsifiability, the IDM offers a robust tool for future research and practical applications. This model significantly advances the theoretical literature on person-environment interactions, providing a holistic understanding that captures the complexity of human experience.